Kualitas Pelayanan Publik pada Website Layanan Aspirasi dan Pengaduan Online Rakyat (LAPOR) di Kabupaten Karanganyar - Melinda Putri Astuti; Is Hadri Utomo (Jurnal Mahasiswa Wacana Publik, 2022)
The public complaint service is a service that facilitates the community in conveying public aspirations and complaints about public services, but the number of reports and users of these services is still relatively small in some areas, one of which is in Karanganyar Regency. Therefore, this research was carried out which aims to describe the quality of public services in public complaints services in the form of People's Aspirations and Online Complaints Service (LAPOR) in Karanganyar Regency. This study will describe the quality of public services in the complaint service using five dimensions of service quality according to Tjiptono (2015), namely tangibles, reliability, responsibility, assurance, and empathy. The research method used is a descriptive qualitative research method. The technique of determining the informants using purposive sampling, selected informants who understand the most in managing the People's Online Aspirations and Complaints Service (LAPOR) website in Karanganyar Regency. Data collection techniques were carried out by unstructured interviews and documentation studies. Documentation studies are used as complementary and supporting data derived from reports or annual records of users/number of reporters on the LAPOR website. Validation of data using triangulation of sources by comparing the results of interviews from each resource person. The data analysis technique uses the analysis of Miles & Huberman in Sugiyono (2016), consisting of stages of data reduction, data presentation, and drawing conclusions/verification.